2016
DOI: 10.1038/srep37031
|View full text |Cite
|
Sign up to set email alerts
|

LbCML38 and LbRH52, two reference genes derived from RNA-Seq data suitable for assessing gene expression in Lycium barbarum L.

Abstract: For quantitative real-time PCR (qRT-PCR) analysis, the key prerequisite that determines result accuracy is the selection of appropriate reference gene(s). Goji (Lycium barbarum L.) is a multi-branched shrub belonging to the Solanaceae family. To date, no systematic screening or evaluation of reference gene(s) in Goji has been performed. In this work, we identified 18 candidate reference genes from the transcriptomic sequencing data of 14 samples of Goji at different developmental stages and under drought stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Both ACT and UBQ are stably expressed in wheat, but not in tomato 24,25 . Gong et al 26 analyzed the expression stability of 18 candidate reference genes of Goji at www.nature.com/scientificreports/ different developmental stages and under drought stress condition. They observed that two novel reference genes LbCML38 and LbRH52 were more stably expressed than the commonly used reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…Both ACT and UBQ are stably expressed in wheat, but not in tomato 24,25 . Gong et al 26 analyzed the expression stability of 18 candidate reference genes of Goji at www.nature.com/scientificreports/ different developmental stages and under drought stress condition. They observed that two novel reference genes LbCML38 and LbRH52 were more stably expressed than the commonly used reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DEGs, constitutively expressed genes can be used to screen stable expression genes suitable for RT-qPCR. In recent years, RNA-Seq data has been used for the selection and validation of more new stable reference genes in many studies, for example in pregnant woman (Chim et al, 2017), human cancer tissue (MacRae et al, 2013), different Streptomyces coelicolor strains (Li et al, 2015), and different developmental stages and drought stress conditions in Goji (Gong et al, 2016). These studies successfully identified new reference genes which are more stable than the traditionally used ones, indicating that selection of stably expressed reference gene from RNA-Seq data is a powerful and reliable method.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have found that the expression levels of HKGs vary to different degrees based on tissues, developmental stages, or experimental conditions ( Thellin et al, 1999 ; Nicot et al, 2005 ; Wu et al, 2016 ). Therefore, it is necessary to select stably expressed HKGs as RGs before they are used to normalize target gene expression by qRT-PCR ( Guenin et al, 2009 ; Gong et al, 2016 ). Up to date, many HKGs, such as 18S ribosomal RNA ( 18S rRNA ), 28S ribosomal RNA ( 28S rRNA ), β-actin ( ACT ), elongation factor 1-alpha ( EF1A ), glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), α tubulin ( TUA ), β tubulin ( TUB ), polyubiquitin ( UBQ ), cyclophilin ( CYP ), SAND protein family ( SAND ), malate dehydrogenase ( MDH ), glyceraledehyde-3-phosphate dehydrogenase of plastid 1 ( GAPCP1 ), and so on, have been used to conducted studies for evaluating their stability under different experimental conditions ( Demidenko, Logacheva & Penin, 2011 ; Chen et al, 2015 ; Cao, Wang & Lan, 2016 ; Ferraz Dos Santos et al, 2016 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%